Determinants Of Consumers' Buying Behaviors For Domestic And Foreign Products : A Malaysian Perspective - Yeoh, Bee Bee (2005)
This study examines the determinants of consumers' buying behaviors for domestic and foreign products. It focuses on the consumers' buying behaviors from the Malaysian consumers' perspective especially for the electrical/electronic products, household appliances and kitchen appliances.